New species and records of Lesteva Latreille, 1797 from China (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2017)
New morphological and faunistic data for eight Chinese species of the genus Lesteva Latreille, 1797 are provided. Two new species are described and illustrated: L. (s.str.) jaechi sp.n. (Guangdong, Yao Shan) and L. (s.str.) schoenmanni sp.n. (Hubei, Shennongjia). The following new synonymy is established: L. (s.str.) dabashanensis Rougemont, 2000 = L. michaeli Rougemont, 2017 syn.n. New provincial records of L. (s.str.) cooteri for Jiangxi and Hubei, L. (s.str.) dabashanensis for Sichuan and Gansu, L. (s.str.) rufopunctata rufopunctata Rougemont, 2000 for Yunnan, and L. (s.str.) pulcherrima for Hubei are provided. The distribution of L. (s.str.) cooteri, L. (s.str.) dabashanensis, L. (s.str.) elegantula, L. (s.str.) pulcherrima and L. (s.str.) rufopunctata rufopunctata are mapped.